Examen especial a la gestión del talento humano del centro ambulatorio IESS, del cantón Gualaquiza de la provincia de Morona Santiago, en el periodo 2014 - Viñan Zamora, Melva Rocio (2016)
Special to Human Resource Management Center Ambulatory IESS, the Canton Gualaquiza of the Province of Morona Santiago, in the period 2014 Examination was developed based on objectives which are: The first specific objective is to evaluate the internal control system of the entity, which was developed by conducting internal control questionnaire to the aforementioned Outpatient Center, the same that was used to meet existing shortcomings within the institution. It also serves a requirement to be eligible for the title of Engineer in Accounting and Auditing. For normal development of the special examination required the collection of information for which the preliminary report to the entity under study knowledge was made, the audit program was developed by using the aforementioned internal control questionnaire; whereby the strengths and weaknesses allowing met issue conclusions and recommendations to improve institutional performance. With the help of the application of methods, techniques and procedures have uncovered the most significant findings to analyze and describe them through so-called narrative ballots. In the end it was concluded that by conducting the internal control system, it was verified that in the aforementioned medical school did not have a manual function, which causes employees have not specified each of its activities to develop. By concluding found, it could issue a recommendation to the Director of Ambulatory IESS Center, prepare a manual of functions which serve to each of the employees who work within it, since it will establish the activities to be of meet employees.